Upaya Peningkatan Kesadaran Masyarakat dalam Penurunan Stunting Melalui Sosialisasi Menu Makanan Bergizi Seimbang - Pratama, Reza; Daulay, Zharifah Zahwa; R. Tanjung, Linda Fitria; Aulia, Syaikah Nabilah; Ramadhani, Sarah; Mayasari, Ulfayani; Ridwan, Muhammad (MENARA RIAU, 2024)
Stunting is a serious health issue in Indonesia, particularly in rural areas like Namo Mbelin Village, Langkat. The aim of this research is to enhance public understanding of the importance of a balanced diet in efforts to reduce stunting through outreach involving pregnant women, prospective brides, and toddlers. This study employs a qualitative approach with a descriptive method, where data is collected through interviews, observations, and document reviews. The results show an increase in public knowledge regarding the importance of balanced nutrition, rising from 30% before the outreach to 70% afterward. Additionally, the community has begun to adopt a balanced diet, with increased consumption of animal protein and vegetables. Cooking demonstrations, such as making quail egg balls, effectively reinforced the community's practical understanding of balanced nutrition. The study concludes that the outreach on balanced nutrition was effective in enhancing understanding and changing community habits to prevent stunting. Ongoing support from various stakeholders is necessary to maintain these positive effects in the long term.